Pengaruh Kompetensi Perangkat Desa, Sistem Pengendalian Internal dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Sidemen Kabupaten Karangasem - I Gede Putra Adnyana (UNHI Press, 2022)
This research was conducted at the Village Government of Sidemen District, Karangasem Regency. The purpose of this study was to determine the effect of village apparatus competence, internal control system and community participation on village fund management accountability in Sidemen sub-district, Karangasem district. The population used in this study were all village officials in the villages of the Sidemen District. The sampling technique used in this research is purposive sampling where the sample in this study is village officials who carry out village fund management in Sidemen District. The number of respondents in this study were 80 respondents. The analytical technique used is multiple linear regression analysis, the coefficient of determination and to test the hypothesis used is the t test and f test using the IBM SPSS Statistics 21 tool. The results of this study found that Village Apparatus Competence had no significant effect on Village Fund Management Accountability, while the Internal Control System and Community Participation have a positive and significant impact on Village Fund Management Accountability.